The Role of Endothelial Microparticle in Coronary Heart Disease as The Complications of Diabetes Mellitus - Elfi, Eka Fithra; Ilhami, Yose Ramda; Darwin, Eryati (Jurnal Biodjati, 2019)
Â Â Coronary heart disease (CHD) is caused by obstruction of coronary blood flow due to endothelial dysfunction triggered by various genetic and non-genetic risk factors such as hyperlipidemia, hypertension, hyperglycemia and obesity. Endothelial cell activation due to hyperglycaemia in diabetes mellitus induces production of pro-inflammatory factors that damage the cell membrane triggering the formation of membrane particles called microparticles. Endothe-lial microparticles contain proteins including endothelial nitric oxide synthase (eNOS) which plays a role in the production of nitric oxide (NO). To determine the role of microparticles in the occurrence of coro-nary heart disease in diabetes mellitus due to endothelial dysfunction, a study was conducted by comparing the levels of eNOS and NO in DM patients who had CHD with DM patients who had no CHD. Blood samples from 20 DM patients who had CHD and 20 DM patients who had no CHD of the outpatients in Cardiology Department and Inter-nal Medicine department of regional public hospital were included in this study. All patients were fulfilled inclusion and exclusion criteria and diagnosed by the appropriate specialist. The eNOS and NO lev-els were measured using the ELISA method. The results of this study show that eNOS levels in the group of DM patients who had CHD (21,292Â±12,415 ng/ml) were significantly lower (p <0.05) than those in the group of DM patients who had no CHD (29,721Â±11,952 ng/ml). Nitric oxide levels in DM patients who had CHD (0,053Â±0,021 nmol/ Î¼l) were not statistically different to the levels in DM patients who had no CHD (0,047Â±0,032 nmol/Î¼l). From the results of this study we concluded that endothelial microparticle protein eNOS plays a role in the occurrence of CHD due to the complications of diabetes mellitusÂ